2008
DOI: 10.1007/s00234-008-0464-9
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor mode in imaging of intracranial epidermoid cysts: one step ahead of fractional anisotropy

Abstract: Thus, advanced imaging modalities like DTI with DTM can provide information regarding the microstructural anatomy of the epidermoid cysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…As observed in the present study, Zhang et al 33 reported decreased CL in brain metastases. Tensor shape measurements have also been used to differentiate subtypes of meningiomas, 38,39 to distinguish true from pseudo-WM tracts inside abscess cavities, 40 and to characterize epidermoid cysts 41,42 and brain tuberculomas. 43 In a previous study, we demonstrated elevated FA, CL, and CP from the ER of glioblastomas in comparison with brain metastases.…”
Section: Shape Of Diffusion Tensor In Brain Tumorsmentioning
confidence: 99%
“…As observed in the present study, Zhang et al 33 reported decreased CL in brain metastases. Tensor shape measurements have also been used to differentiate subtypes of meningiomas, 38,39 to distinguish true from pseudo-WM tracts inside abscess cavities, 40 and to characterize epidermoid cysts 41,42 and brain tuberculomas. 43 In a previous study, we demonstrated elevated FA, CL, and CP from the ER of glioblastomas in comparison with brain metastases.…”
Section: Shape Of Diffusion Tensor In Brain Tumorsmentioning
confidence: 99%
“…Despite the advantage of using sets of orthogonal invariants (K i or R i ), there is a tremendous volume of literature that analyzes DT-MRI data by evaluating the tensor trace ðK 1 Þ and FA ðR 2 Þ, which has given rise to a body of knowledge and expectation about the values of these invariants and how they are altered by disease (Sotak, 2002;Thomalla et al, 2004;Jolapara et al, 2009). Note that K 1 is not orthogonal to R 2 (see Ennis and Kindlmann (2006)).…”
Section: Non-orthogonal Tensor Invariant Setmentioning
confidence: 99%
“…Histological examination of the tumor confirmed the structured parallel orientation of internal contents. A very recent study published during the review process of this article has shown that a "tensor mode value" approaching -1 also suggests diffusion along a geometric plane (23).…”
Section: Discussionmentioning
confidence: 90%